Экономический механизм и активизация человеческого фактора - Андриенко В. Е. Владимир Ефимович; Шамота В. Н. Владимир Николаевич; Нныпко А. С. Александр Сергеевич; Федоренко А. В. Анатолий Васильевич (Киев, Наукова думка, 1990)
Исключено из фонда НТБ ТПУ